Privacy Considerations for a Pervasive Eye Tracking World - Liebling, Dan; Preibusch, Sören (4th International Workshop on Pervasive Eye Tracking and Mobile Eye-Based Interaction, 2014)
Multiple vendors now provide relatively inexpensive desktop eye and gaze tracking devices. ith miniatureization and decreasing manufacturing costs, gaze trackers will follow the path of webcams, becoming ubiquitous and inviting many of the same privacy concerns. However, whereas the privacy loss from webcams may be obvious to the user, gaze tracking is more opaque and deserves special attention. In this paper, we review current research in gaze tracking and pupillometry and argue that gaze data should be protected by both policy and good data hygiene.